Traversing Borders: The Role of Vignettes in Depicting Globalisation in Mohsin Hamid’s Exit West - Humaira Yousaf; Noreen Shah; Muhammad Hussain Damsaz; Sahar Sher (Dialogue Social Science Review (DSSR), 2025)
This study explores the significance of various vignettes in Mohsin Hamid's novel Exit West to elucidate Globalization's social and cultural dimensions. Through these vignettes, Hamid portrays the agonizing experiences of migrants who strive to adjust their cultural and social norms to survive in Western societies, often feeling separated and estranged. The research aims to establish connections between the vignettes and the broader context of Globalization, focusing on the characters' desires for escape, their struggles with assimilation, and the creation of hybrid cultures. The study uses Stuart Hall's Representation and Coding/Decoding theories to analyze how Hamid's narrative techniques reflect the complex realities of migration, displacement, and cultural conflict in the contemporary global landscape. The findings highlight how Globalization influences individual identities and relationships, emphasizing the perpetual state of flux and transformation within societies. This research contributes to the understanding of Globalization's impact on literature and the lived experiences of migrants, offering insights into the broader implications of cultural integration and resistance.